Advances in hydrogen-enriched biogas/biodiesel combustion for near-zero emissions in direct injection engines - Md. Nasar Equbal; Ashok Kumar Dewangan; Syed Quadir Moinuddin; Aqueel Ahmad; Ashok Kumar Yadav (International Journal of Thermofluids)
Alternative fuels like biogas, biodiesel, and hydrogen are gaining traction as sustainable solutions to reduce fossil fuel dependency and mitigate environmental pollution. This review examines the performance, combustion, and emission characteristics of compression ignition dual-fuel diesel engines utilizing these fuels. Key performance indicators, including brake thermal efficiency (BTE), brake-specific fuel consumption (BSFC), peak cylinder pressure (PCP), ignition delay, and emission metrics carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx), particulate matter (PM), and carbon dioxide (CO2), are thoroughly analyzed. Biogas usage leads to a 2–20 % reduction in BTE, up to 35 % higher BSFC, and an 18–55 % decrease in NOx and smoke emissions, but increases HC and CO emissions by up to 30 %. In compare, hydrogen and biodiesel improve BTE by up to 10 %, reduce HC and CO emissions by 40–50%, but increase NOx emissions by 20 %. Biogas exhibits lower PCP (10–15 %), flame temperature (1600–1800 K), and extended burn duration (40–50 °CA). Biodiesel demonstrates moderate PCP (5–10 %), flame temperature (2000–2200 K), and shorter burn duration (35–40 °CA). Hydrogen outperforms both fuels with the highest PCP (15–20 %), flame temperature (2300–2500 K), and rapid burn duration (25–30 °CA), achieving combustion efficiency greater than 95 %, albeit with elevated NOx levels. These findings highlight the potential of alternative fuels to enhance engine performance, optimize combustion characteristics, and reduce harmful emissions, contributing to cleaner energy and sustainable development.